2019
DOI: 10.1051/0004-6361/201936666
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mixing in low mass stars

Abstract: Context. When modelling stars with masses higher than 1.2 M⊙ with no observed chemical peculiarity, atomic diffusion is often neglected because, on its own, it causes unrealistic surface abundances compared with those observed. The reality is that atomic diffusion is in competition with other transport processes. Rotation is one of the processes able to prevent excessively strong surface abundance variations. Aims. The purpose of this study is to quantify the opposite or conjugated effects of atomic diffusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 70 publications
8
67
0
Order By: Relevance
“…Turbulent mixing helps to avoid strong surface abundance variations of all chemical elements, but it is not efficient enough to bring Li down to its nuclear destruction region. On the contrary, rotation can induce a Li destruction but cannot reduce strong surface abundance variations of chemical elements (Deal et al 2020). Indeed, the 1.0 M model, which includes rotational mixing, reduces the surface Li abundance by more than one order of magnitude.…”
Section: The Impact Of Atomic Diffusion and Mixing On Chemical Abundamentioning
confidence: 98%
See 2 more Smart Citations
“…Turbulent mixing helps to avoid strong surface abundance variations of all chemical elements, but it is not efficient enough to bring Li down to its nuclear destruction region. On the contrary, rotation can induce a Li destruction but cannot reduce strong surface abundance variations of chemical elements (Deal et al 2020). Indeed, the 1.0 M model, which includes rotational mixing, reduces the surface Li abundance by more than one order of magnitude.…”
Section: The Impact Of Atomic Diffusion and Mixing On Chemical Abundamentioning
confidence: 98%
“…We considered the magnetised wind braking of Matt et al (2015Matt et al ( , 2019 and an additional vertical viscosity of ν v = 10 8 cm 2 s −1 as calibrated by Ouazzani et al (2019) to take into account the fact that the current rotation theory underestimates the transport of angular momentum. The other aspects of these models are the same as the ones presented in Deal et al (2020). These models are only used to show that rotation may explain Li depletion on the main sequence.…”
Section: Modelling Transport Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deal et al (2018) showed that this is an important process when inferring the properties of main-sequence stars. Deal et al (2020) further showed that modest rotation (about 30 km s −1 ) is insufficient to prevent a discernible effect on the stellar properties. Given that HD 38529 probably rotated more slowly, it may have experienced significant heavy element enhancement at its surface on the main sequence, even if much of the effect has since been erased by the growing convective envelope.…”
Section: Neglected Transport Mechanismsmentioning
confidence: 98%
“…To roughly quantify the effect of these neglected processes, we first computed evolutionary tracks up to the observed eff = 5578 K with = 1.48 M , [Fe/H] = 0.34 and a rotation rate of 5 d at age 10 Myr as described in Deal et al (2020). Each track used one of the following combinations of the extra chemical transport processes above: rotation, gravitational settling and radiative levitation; gravitational settling and radiative levitation; only gravitational settling; and no extra chemical transport.…”
Section: Neglected Transport Mechanismsmentioning
confidence: 99%